2020
DOI: 10.3390/en13071702
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort Aspects of Solar Gains during the Heating Season

Abstract: Glazing plays a key role in the energy balance of buildings. The aim of this paper is to enlighten the thermal discomfort caused by large glazed areas in the heating season and to point out a possible solution that can provide proper thermal comfort with low energy use. It is unusual to discuss the negative effects of solar gains on thermal comfort during the heating season. However, there are cases when glazing may lead to unforeseen indoor thermal discomfort conditions. Laboratory and on site measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…It has been proven that indoor thermal comfort has particular importance since it interacts with occupants' health and productivity and buildings' energy performance [89]. In the initial design phase of new energy-efficient buildings or during the implementation of energy retrofitting projects, it is crucial to incorporate considerations for thermal comfort [53,90]. The proper orientation of the facades and the appropriate layout of rooms can help avoid thermal discomfort [90].…”
Section: Impacts Of Glazing Systems On Buildings' Thermal Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that indoor thermal comfort has particular importance since it interacts with occupants' health and productivity and buildings' energy performance [89]. In the initial design phase of new energy-efficient buildings or during the implementation of energy retrofitting projects, it is crucial to incorporate considerations for thermal comfort [53,90]. The proper orientation of the facades and the appropriate layout of rooms can help avoid thermal discomfort [90].…”
Section: Impacts Of Glazing Systems On Buildings' Thermal Comfortmentioning
confidence: 99%
“…In the initial design phase of new energy-efficient buildings or during the implementation of energy retrofitting projects, it is crucial to incorporate considerations for thermal comfort [53,90]. The proper orientation of the facades and the appropriate layout of rooms can help avoid thermal discomfort [90]. The significance of glazing systems for indoor thermal comfort cannot be disregarded, particularly when selecting a suitable glazing solution.…”
Section: Impacts Of Glazing Systems On Buildings' Thermal Comfortmentioning
confidence: 99%
“…Soutullo et al [9] compared the impact of three different climates on the energy performance of a Madrid house to arrive at potential design strategies. Kalm et al [10] have demonstrated experimentally that the use of advanced personalized ventilation systems can provide adequate thermal comfort without reducing daylight performance. Oh et al [11] proposed five new pre-screening analysis methods, using interval data recorded by smart meters to analyze the energy saved by installing home automation devices.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Other studies [34][35][36][37][38][39][40][41] have highlighted the differences in the theoretical and real effects of thermomodernization. In the group of educational buildings located in the city of Bialystok, a 33% reduction in energy consumption was achieved, while the planned reduction in energy consumption was approximately 59-71% [34].…”
Section: Introductionmentioning
confidence: 99%
“…This aspect was also dealt with by Brom et al [37] and they found that about 50% of the differences in heat consumption between the same buildings can be explained by the characteristics of the building itself and other physical parameters and the remaining 50% of differences may result from the behavior of occupants. Many studies [38][39][40][41] also emphasize the influence of solar radiation on the building's energy demand for heating, and thus on the effects of thermomodernization.…”
Section: Introductionmentioning
confidence: 99%